Holistic-textual Approach to Qur'anic Verses on Muslim-Jewish Relationship in the Qur'an - Dr. Alwani Binti Ghazali; Muhammad Kamal; Zamrie Ibrahim @ Musa (Human Resource Management Academic Research Society, 2024)
Non-Indexed Publication